Teacher Appreciation in Educating Students in Telkom Makassar Elementary School - Khaerunnisa; Rahayu Muslimin, Rika; Rosdiana (CV Kalimasada Group, 2024)
This study aims to describe the application of appreciation by teachers at SD Telkom Makassar and its impact on learners' motivation and development. Appreciation, both verbal and nonverbal, plays an important role in creating a positive learning environment, increasing self-confidence, and motivating learners to try harder. The research used a qualitative approach with a descriptive method. Data were collected through in-depth interviews, direct observation, and documentation of learning activities. The results show that appreciation applied by teachers in the form of verbal praise, symbolic awards such as certificates and certificates, and personal attention is effective in increasing students' motivation. The award program that is carried out regularly provides recognition that strengthens the spirit of healthy competition among learners. Although there are constraints related to time and appropriateness of the form of appreciation, the application of appreciation is proven to strengthen the relationship between teachers and learners and encourage their development holistically.